Determination of Photoacoustic Detection in Michelson Interferometer Cavity - Mohammad I. Abu Taha; Ahmed S. Jabr (New Trends in Physical Science Research Vol. 3, 2022)
We report photoacoustic (PA) signal detection in a cell placed within the Michelson interferometer cavity in an attempt to relate photoacoustic effect to the Michelson fringe shift as a result of changes in the cell. Both detection schemes were investigated using IR absorp- tion and their sensitivities compared. Photoacoustic spectroscopy (PA) is a type of photothermal spectroscopy in which the absorbed energy is released as a localised pressure wave, or sound wave. Signals related to the Michelson interferometer fringe and the PA effect have shown good relationships with each other utilising a variety of materials, including essential oils and the plant parts from which they are often extracted. Results were encouraging and will open the door widely to use the combined Michelson interfe- rometer-photoacoustic spectroscopy (PAS) in trace gas detection for different applications. Simultaneous detection of both signals utilising the novel combination technology offers an alternative to costly lasers, which are substituted by a low-cost wideband-pulsed IR source with good capabilities in the field of portable trace gas detection systems.